Kontrakty regionalne i ocena ich funkcjonowania na przykładzie województwa podkarpackiego - Kudełko, Joanna (The Regional Contracts and Their Evaluation for the Podkarpackie Region, 2005)
This article presents the functioning of the so-called regional contract, a new tool for stimulation of regional development in Poland. The supporting terms of regional contracts in that form are included in the Support Program, accepted by the Cabinet. The regional contracts were introduced to promote the socio-economic development, increase the range of country decentralization and concentrate the finance for the regional development and its rationalization. This paper shows the realization of the regional contract for the Podkarpackie Region in 2001-2003. In it were evaluated the economic results of the contract.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 252-268